The effect of air-abrasion on the susceptibility of sound enamel to acid challenge. (March 2016) - Johnson King, O.; Milly, H.; Boyes, V.; Austin, R.; Festy, F.; Banerjee, A.
Abstract: Objective: To evaluate the effect of air-abrasion using three abrasive powders, on the susceptibility of sound enamel to an acid challenge. Methods: 40 human enamel samples were flattened, polished and assigned to 4 experimental groups ( n  = 10); a: alumina air-abrasion, b: sodium bicarbonate air-abrasion, c: bioactive glass (BAG) air-abrasion and d: no surface treatment (control). White light confocal profilometry was used to measure the step height enamel loss of the abraded area within each sample at three stages; after sample preparation (baseline), after air-abrasion and finally after exposing the samples to pH-cycling for 10 days. Data was analysed statistically using one-way ANOVA with Tukey's HSD post-hoc tests ( p  < 0.05). Unique prismatic structures generated by abrasion and subsequent pH cycling were imaged using multiphoton excitation microscopy, exploiting strong autofluorescence properties of the enamel without labelling. Z -stacks of treated and equivalent control surfaces were used to generate non-destructively 3-dimensional surface profiles similar to those produced by scanning electron microscopy. Results: There was no significant difference in the step height enamel loss after initial surface air-abrasion compared to the negative control group. However, a significant increase in the step height enamel loss was observed in the alumina air-abraded samples after pH-cycling compared to the negative control ( p  < 0.05). Sodium bicarbonate as well as BAG air-abrasion exhibited similar enamel surface loss to that detected in the negative control group ( p  > 0.05). Surface profile examination revealed a deposition effect across sodium bicarbonate and BAG-abraded groups. Conclusion: This study demonstrates the importance of powder selection when using air abrasion technology in clinical dentistry. Pre-treating the enamel surface with alumina air-abrasion significantly increased its susceptibility to acid challenge. Therefore, when using alumina air-abrasion clinically, clinicians must be aware that abrading sound enamel excessively renders that surface more susceptible to the effects of acid erosion. BAG and sodium bicarbonate powders were less invasive when compared to the alumina powder, supporting their use for controlled surface stain removal from enamel where indicated clinically.